Теоретичне обгрунтування фільтрації грунтових вод і міграції забруднень і добрив у районах зрошення земель - Волошкіна, О.С.; Кремез, В.С.; Олійник, О.Є. (Екологічна безпека та природокористування, 2012)
A scientific ground is executed on posterization of hydrogeological and hydrochemical terms and on their basis the mathematical model of filtration of gruntovikh waters and migration of contaminations and fertilizers is built in the districts of the irrigated earths and adjoining territories. A general model consistsof two blocksbetween itself : hydrodynamic (lauter) block and block of dynamics of migration and transformation of contaminations and fertilizers in a filter porous environment. For different charts and models of filtration and migrations are resulted necessary equalizations and terms.